2003
DOI: 10.1046/j.1523-1747.2003.12039.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Hepatocyte Growth Factor Leads to Retarded Cutaneous Wound Healing Associated with Decreased Neovascularization and Granulation Tissue Formation

Abstract: To elucidate biologic functions of hepatocyte growth factor and the c-Met receptor in cutaneous wound healing, we analyzed expression and localization of hepatocyte growth factor and c-Met receptor and used a strategy to neutralize endogenous hepatocyte growth factor in a cutaneous wound healing model in mice. Following excision of full-thickness skin on the dorsum of mice, expression of both hepatocyte growth factor and the c-Met receptor increased transiently in cutaneous tissues. Expressions of hepatocyte g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 35 publications
3
64
1
Order By: Relevance
“…Previous reports using an inhibitory anti-HGF antibody have shown that HGF is essential for protection of the heart 27 and lungs 51 from reperfusion injury, maintenance of kidney function following obstructive nephropathy, 52 and wound healing in the skin. 53 In the current study, we showed that treatment of bleomycin-injured PAI-1 Ϫ/Ϫ mice with this inhibitory anti-HGF antibody worsened pulmonary fibrosis while a control antibody did not. This result suggests that in vivo neutralization of HGF lessens the protection that PAI-1 deficiency confers on bleomycin-induced pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 48%
“…Previous reports using an inhibitory anti-HGF antibody have shown that HGF is essential for protection of the heart 27 and lungs 51 from reperfusion injury, maintenance of kidney function following obstructive nephropathy, 52 and wound healing in the skin. 53 In the current study, we showed that treatment of bleomycin-injured PAI-1 Ϫ/Ϫ mice with this inhibitory anti-HGF antibody worsened pulmonary fibrosis while a control antibody did not. This result suggests that in vivo neutralization of HGF lessens the protection that PAI-1 deficiency confers on bleomycin-induced pulmonary fibrosis.…”
Section: Discussionsupporting
confidence: 48%
“…Many types of cells, including platelets (3), neutrophils (4), macrophages (5), mast cells (6), fibroblasts (7) and keratinocytes (8) are also involved in steps leading to healing of the wound. In addition, cellular processes, such as angiogenesis (9), fibroplasia and granulation tissue formation (10,11), collagen deposition (12) and epithelialization (13) contribute to the repair. Although the process of wound healing has been extensively studied, unresolved issues remain, including those surrounding the interplay between environmental and genetic factors, which allow the healing process to occur normally.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HGF is capable of stimulating migration and proliferation of keratinocytes and thus has been suggested to be involved in cutaneous physiology and wound healing [17,18]. HGF inducers may also be useful as therapeutic agents for these diseases.…”
Section: Introductionmentioning
confidence: 99%